Epidemiological model for the construction of scenarios of the dissemination of COVID-19 in Codó-MA - Lisboa dos Santos, Antonia (2023)
Background and objectives: due to the increase in the number of cases of the new coronavirus in the city of Codó-MA, there was a need to carry out a study on the spread of COVID-19 in the municipality in order to have a better knowledge and understanding of the problem. A study was carried out on the spread of COVID-19 in the city of Codó-MA, comparing the quantitative data on the number of cases in 2020 and 2021 between May and July and using the epidemiological model Susceptible-Infectious-Isolated-Recovered (SIQR). Methods: we collected daily data from the epidemiological bulletins made available by the Municipal Health Department of Codó (SEMUS-Codó), we chose the SIQR compartmental model to carry out the simulations, we assumed hypotheses and estimated the parameters in order to design the scenarios. We simulated scenarios such as social distancing of healthy individuals and social isolation of infected individuals. Results: in early 2020, cases increased more frequently than in early 2021, and approximately 20% of those infected were in social isolation. According to projections, more than 80% of cases of COVID-19 were not accounted for in Codó. In 2021, there was greater underreporting than in 2020, approximately 82% and 85%, respectively. Conclusion: from the results, the authors conclude that the social isolation of those infected is a more efficient method to contain an epidemic than the total blockade of the population and that the high number of underreported cases is because most of these cases are asymptomatic.